Some alkylation reactions in organic synthesis - Siti Fatimah Abd. Rahim, 1989-; Hasnah Mohd. Sirat, supervisor; Fakulti Sains (2011)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2011